RecA-Mediated Affinity Capture: A Method for Full-Length cDNA Cloning. (October 1999) - Zhumabayeva, Bakhyt; Chenchik, Alex; Siebert, Paul D.
We describe an improved method for rapid cloning of full-length cDNA from cDNA libraries. This approach is based on the ability of Escherichia coli RecA protein to form a stable nucleoprotein complex with a linear single-stranded DNA probe and homologous sequences in circular double-stranded DNA. Hybridization of RecA-coated biotinylated DNA probes to homologous plasmid DNA creates triple-stranded complexes, which are then captured on streptavidin-coated magnetic beads. Following magnetic separation of the hybrid molecules, the enriched plasmid population is recovered by alkaline treatment, precipitated, resuspended and used to transform bacteria. Typically, many clones can then be recovered by colony hybridization screening of a single plate of the enriched library. We have used this technology to clone fulllength and alternatively spliced forms of the human bcl-xL cDNA from a human liver cDNA library.